Inscripciones y grafitos tartésicos de la necrópolis orientalizante de Medellín (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Three Tartessian inscriptions have been found in the orientalizing cemetery of Medellín (Badajoz, Spain) and 11 graffiti with marks or decorations. The graffiti go back to the VII century BC, and the tartessian inscriptions are dated throughout the VI century BC. They document the use of writing in this tartessian town, where graffiti and epigraphs correspond to an urban context. The most interesting inscription is a stele typologically related to those ones found in Southern-Portugal. It proves that the orientalizing people of Medellín and Southern Portugal were Tartessian, with the same language and writing. Two other graffiti inscriptions on pottery confirm the use of writing in mortuary contexts and document the transition of writing from right to left to left to right in the second half of the VI century BC. This local evolution of writing in Medellín also proofs the existence of different local scripts in the Tartessian world.